Pemberdayaan Keluarga dalam Pendampingan Penanganan Luka Ulkus Diabetes Melitus Type 2 di Kelurahan Labuang Baji Kecamatan Mamajang Kota Makassar - Maria, Ida Leida; Wahiduddin, Wahiduddin; Thaha, Ridwan M.; Firman, Firman (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2024)
South Sulawesi is one of the provinces with the prevalence of diabetes mellitus which continues to increase by 23% in 2022. Labuang Baji sub-district of Makassar city is one of the sub-districts with the highest number of diabetes mellitus patients with wounds/ulcers. This community service is intended to provide education and support to families on how to treat diabetic ulcers. Assistance was given to families (30 people) through communication, information, motivation and education methods through counseling and questionnaires. Tests were given before and after the assistance, then data were analyzed using the McNemer and Wilcoxon tests. Family knowledge before assistance was (36.7%) with poor knowledge, (63.3%) with good knowledge. After the assistance, the family's knowledge increased to (96.7%) good knowledge with an average increase in pre-test and post-test scores of 2.7 times. Based on the T-test, the p-value (<0.05) was obtained. So it can be concluded that the assistance of handling Type 2 diabetes mellitus ulcers in Labuang Baji Village, Mamajang Subdistrict, Makassar has a significant impact on the participants.